The Establishment Village Regulation of Problematic in West Sulawesi Province Reviewed from a Sociology of Law Perspective - Astomo, Putera Astomo; Rais, M. Tasbir (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
The establishment of village regulations in West Sulawesi Province creates problems, especially in sociology of law perspective because it is closely related to the lives of village communities which were regulated in a village regulations betweens: 1) The lack of knowledge of village government officials in the establishment of village regulations. 2) The village regulations drafts were not socialized by village government officials regarding asking for input from the communities until it was passed into a village regulation. 3) The village regulations cannot be implemented. The problems formulation includes: 1) How is the relationship betweens the establishment legislation of principles with the establishment of village regulations in sociology of law perspective? 2) How is forms of problems arise in the establishment of village regulations in West Sulawesi Province were reviewed from a sociology of law perspective? The type of research was sociolegal research. The results show that’s: 1) The relationship betweens the establishment legislation of principles with the establishment of village regulations in sociology of law perspective can be seen in efforts to uphold internal sociological values of establishment legislation of principles. 2) Forms of problems arise in the establishment of village regulations on West Sulawesi Province were viewed from a sociology of law perspective betweens: a) The type, hierarchy and content of village regulations were not appropriate. b) Cannot be implemented. c) The formulation was not clear. d) Don’t open.